Acute Effects of Static Self-Stretching Exercises and Foam Roller Self-Massaging on the Trunk Range of Motions and Strength of the Trunk Extensors - Maria Fonta; Elias Tsepis; Konstantinos Fousekis; Dimitris Mandalidis (MDPI AG, 2021)
Although the effectiveness of static self-stretching exercises (SSSEs) and foam roller self-massaging (FRSM) in joint range of motion and muscle strength of the lower limbs has been extensively investigated, little is known about their effectiveness on the posterior trunk muscles. The present study aimed to investigate the acute effects of two 7-min SSSEs and FRSM intervention protocols on the range of trunk movements and the strength of the trunk extensors. Twenty-five healthy active males (n = 14) and females (n = 11) performed each intervention separately, one week apart. The range of motion (ROM) of the trunk-hip flexion (T-HF), the ROM of the trunk side-flexion (TSF) and rotation (TR) bilaterally, as well as the isometric maximum strength (TESmax) and endurance (TESend) of the trunk extensors were measured before and after each intervention. The ROMs of T-HF, TSF, and TR were significantly increased following both SSSEs and FRSM. The TESmax and TESend were also significantly increased after FRSM, but decreased following SSSEs. While both interventions were effective in increasing the range of motion of the trunk, a single 7-min session of FRSM presented more advantages over a similar duration SSSEs protocol due to the increase in the strength of the trunk extensors it induced.